Palliative care and public health: an asymmetrical relationship?. (February 2019) - Whitelaw, Sandy; Clark, David
Interest in the potential for public health and palliative care to work together is now widely established. Based on a mapping review of existing literature, we describe for the first time the ways in which public health has entered palliative care policy and practice and how this has been specifically articulated. We then go on to pursue analytical and critical lines of enquiry that are largely absent from the existing literature. We do this in three ways: (i) by considering why the link between public health and palliative care has become so ubiquitous within palliative care policy; (ii) by establishing how this has been constructed; and (iii) by exploring public health as a 'reference discipline' from which its 'secondary deployment' can become embedded inside another disciplinary field. From this, we develop a range of critical perspectives on the relationship between public health and palliative care by scrutinising its claims of utility and effectiveness and questioning the strength of the interdisciplinary interaction between the two disciplines. We see their relationship in a 'cross disciplinary' context which is still largely symbolic and tactical in nature. We conclude by considering the significance of these insights for policy and practice, with two possible scenarios. If the use of public health is essentially figurative and its resources are not unique, the particular and exclusive use of the term becomes insignificant. Progressive and effective policy and practice is possible, independent of any explicit public health label. If however public health is considered to have intrinsic and definable worth, we suggest that this currently asymmetrical association needs to be significantly developed with much higher levels of theoretical, practical and critical engagement between the two disciplines. Such work would result in more reflective and robust policy and practice.